Grain and Seed Proteins Functionality 2021
DOI: 10.5772/intechopen.95323
|View full text |Cite
|
Sign up to set email alerts
|

Pea Seed Proteins: A Nutritional and Nutraceutical Update

Abstract: Grain legumes are well known as staple sources of soluble protein worldwide. Pea is essentially the most quickly growing crop for immediate human consumption and has the potential for higher effect as being a protein supply for foods processing apps. Pea seeds are an essential source of plant-based proteins. The better acceptance of pea protein-rich food is due to pea manifold attributes, excellent functional qualities, high vitamin value, accessibility, and comparatively small cost. Pea proteins are not merel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
(118 reference statements)
1
6
0
1
Order By: Relevance
“…The absence of a direct relationship between the total protein concentration and the level of the AOX protein could be expected, since the AOX is only a part of the total protein concentration [20]. In fact, the values of total protein concentration essentially reflect the concentration of storage proteins, which is variable among cultivars [21]. Moreover, studies focused on the protein composition of pea seeds showed that a large percentage of the identified proteins correspond to storage proteins (mainly albumin, legumin, and vicilin), with the rest being involved in the response to biotic and abiotic stress, energy production, metabolism, and storage of essential non-protein compounds [21].…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a direct relationship between the total protein concentration and the level of the AOX protein could be expected, since the AOX is only a part of the total protein concentration [20]. In fact, the values of total protein concentration essentially reflect the concentration of storage proteins, which is variable among cultivars [21]. Moreover, studies focused on the protein composition of pea seeds showed that a large percentage of the identified proteins correspond to storage proteins (mainly albumin, legumin, and vicilin), with the rest being involved in the response to biotic and abiotic stress, energy production, metabolism, and storage of essential non-protein compounds [21].…”
Section: Resultsmentioning
confidence: 99%
“…Растительный белок может использоваться в качестве заменителя животного белка для удовлетворения пищевых потребностей лакто-вегетарианцев и, таким образом, может сделать пищу более здоровой. Исследователи работают над частичной или полной заменой молочных белков гороховым белком и влиянием на вкус и структуру этих продуктов [41][42][43][44][45][46]. В работе Amagliani [47] обсуждаются исследования ученых белка гороха в качестве инкапсулирующего материала, который является безопасным для здоровья человека, благодаря отсутствию генетических модификаций и не вызывающих аллергических реакций у человека.…”
Section: таблица 3 содержание водорастворимого белка в семенах гороха...unclassified
“…Thus these beds that are occupied with thick fungal growth are harvested at a time after complete growth of the fungus. This system is also suitable for mixed inoculums as well [27].…”
Section: Production System With Substratementioning
confidence: 99%